"Living the life I want": A framework for planning engagement with people with intellectual disability and complex support needs. Issue 2 (24th October 2018) - Dew, Angela; Collings, Susan; Dillon Savage, Isabella; Gentle, Emma; Dowse, Leanne
Abstract: Background: Self‐determination involves autonomy, agency, choice and control. This study investigated how these aspects of self‐determination relate to engaging people with intellectual disability and complex support needs in setting goals and making plans. Method: Body mapping was used to understand the planning experiences of 30 adults with intellectual disability and complex support needs. Each participant created two body maps using a guided group‐based process. Visual and text data were thematically analysed and a framework for planning engagement developed. Results: The framework identifies the centrality of having a well‐developed sense of self which includes insight, motivation and agency, and which is shaped by contextual barriers and facilitators and influenced by helpful and unhelpful support. Conclusions: A well‐developed sense of self and ability to harness resources and people is fundamental to the ability of individuals with intellectual disability and complex support needs articulating goals, identifying aspirations, and attaining valued outcomes.